2013
DOI: 10.4172/2161-0932.1000182
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Late Preterm Births: A Case-Control Study

Abstract: *Corresponding author:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(30 reference statements)
2
1
0
Order By: Relevance
“…In our study, we did not find any significant association of LPT birth with parity, which is in line with the data reported by a case-control study in 5 Italian Centers [25]. However, in a study conducted over 10 years to estimate outcomes of LPT deliveries, a significantly increased prevalence of late preterm birth in multiparous patient was reported [26].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we did not find any significant association of LPT birth with parity, which is in line with the data reported by a case-control study in 5 Italian Centers [25]. However, in a study conducted over 10 years to estimate outcomes of LPT deliveries, a significantly increased prevalence of late preterm birth in multiparous patient was reported [26].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, there were no significant differences between TTN cases and healthy control groups regarding gravidity and parity, and this agreed with Algameel (2020) who found no significant association of late preterm birth who are susceptible to respiratory distress and TTN with parity, which in line with data reported by a case control study in 5 Italian Centers (Mandruzzato et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Mandruzzato et al also supported our findings. 5 Association of previous abortion whether induced or spontaneous with late preterm birth is still not clear. In their review Throp et al reported an increase risk of preterm birth among women who previously had induced abortion.…”
Section: Melamed Et Al In 2008mentioning
confidence: 99%